Six sigma practices integrated with IR 4.0 for sustainability in Malaysian healthcare industry - Diekola Akanmu; Norshahrizan Nordin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Provision of safe, reliable, and affordable care while improving performance and efficiency remains a challenge in the healthcare sector. This study, therefore, reviews the previous researches on the effect of six sigma and industrial revolution 4.0 technologies (IR 4.0) on sustainability as there is still a paucity of literature on the implementation of the practices in the healthcare sector. Notably, the growing challenges within service organizations have motivated healthcare organizations to upgrade their conventional delivery system to a smart sophisticated system. Thus, this present study makes an attempt to model these practices as integrated with IR 4.0 technologies into achieving sustainability in the healthcare industry. In order to fill the void of this gap, this study intends to investigate the joint effects of six sigma and IR 4.0 technologies on sustainable performance of healthcare delivery services. The study confirms the future direction of the public health sector that is recently employing new technologies in its service systems. The data shall be collected from the top management employees, the health practitioners who are working and familiar with the services and operations of the organization and are familiar with the smart tools to expedite services for healthcare. This study extends the current literature on IR 4.0 technologies and six-sigma as enablers of economic, environmental and social sustainability. This study unfolds the significant contribution of operations management practices and how sustainable performance can be enhanced through performance variation and strategic implementation of modern technologies in the healthcare sector.